Аn honor graduate of the kyiv state medical academy - Yurii Voronyi - Dmytro Dubenko (Bogomolets National Medical University, 2021)
The article highlights the historical aspects of a graduate of the Kyiv State Medical Academy in 1921 - Yurii Voronyi's biography. Based on archival documents, the article shows the chronology of his work period at the Kyiv Medical Institute in the early 20s of the last century. The research describes Yurii Voronyi's clinical practice in the faculty surgical clinic of the Kyiv Medical Institute, his Kharkiv's medical period. The paper presents biographical facts about professor Yevgen Chernyakhivskyi - one of Yurii Voronyi's mentors, and his experimental research on vascular surgery and organ transplantation.